Increasing Consumer Buying Interest In B2c Marketplace: Use Of Paid Promote And Live Streaming Seo Techniques - Lena Nofrianti; Andi Azhar (Penerbit Jurnal Indonesia, 2024)
This research aims to determine the effect of SEO Paid Promote and Live Streaming on consumer buying interest in the B2C Marketplace Shopee with Online Customer Reviews as a mediating variable. The object of this research is Shopee Marketplace users in large cities in Indonesia, with 138 respondents selected using the purposive sampling method. Data was collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with Structural Momet Analysis (AMOS) software. The results of this research show that the use of SEO Paid Promote and Live Streaming has a significant effect on Online Customer Reviews and Consumer Purchase Interest. However, Online Customer Reviews only play a mediating role in the influence of Live Streaming on Consumer Buying Interest, while they do not play a mediating role in the influence of SEO Paid Promote on Consumer Buying Interest. The results of the research from the hypothesis obtained SPP (X1) on OCR t value = 2,000 > t table = 1,977 with a significant level (p = 0.04 < 0.05), LS (X2) on OCR (Z) t value calculated = 4,486 > t table = 1,977 with a significant level (p=0.00 < 0.05), SPP (X1) to MB (Y) t calculated value = 2,435 > t table = 1,977 with a significant level (p=0, 01 < 0.05), LS (X2) to MB (Y) calculated t value = 4.163 > t table = 1.977 with a significant level (p = 0.00 < 0.05), OCR (Z) to MB (Y) calculated t value = 2.266 > t table = 1.977 with a significant level (p=0.02 < 0.05), SPP (X1) on MB (Y) via OCR (Z) as a mediating variable calculated t value = 1.505 > t table = 1.977 with a significant level (p=0.12 < 0.05), and LS (X2) on MB (Y) via OCR (Z) as a mediating variable calculated t value = 2.027 > t table = 1.977 with a significant level (p =0.02 < 0.05).